2019
DOI: 10.4014/jmb.1906.06032
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Lactobacillus Fermentation on the Anti-Inflammatory Potential of Turmeric

Abstract: Curcumin, the major bioactive constituent of turmeric, has been reported to have a wide range of pharmacological benefits; however, the low solubility in water has restricted its systemic bioavailability and therapeutic potential. Therefore, in the current study, we aimed to investigate the effect of turmeric fermentation on its curcumin content and anti-inflammatory activity by using several lactic acid bacteria. Fermentation with Lactobacillus fermentum significantly increased the curcumin content by 9.76% w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 34 publications
(42 reference statements)
3
28
0
Order By: Relevance
“…Vitamin D and curcumin have both shown positive effects on the intestinal microbiome, in particular the lactobacilli, which synergistically support probiotic therapy [106,107].…”
Section: Considerations On Perioperative Pharmacologic Prophylaxismentioning
confidence: 96%
“…Vitamin D and curcumin have both shown positive effects on the intestinal microbiome, in particular the lactobacilli, which synergistically support probiotic therapy [106,107].…”
Section: Considerations On Perioperative Pharmacologic Prophylaxismentioning
confidence: 96%
“…Fermentation of plant-based products commonly increases the bioactive phenolic compounds and enhances their antioxidant activity [ 44 ]. In this study, fermentation was observed to increase the anti-inflammatory properties of IAME.…”
Section: Discussionmentioning
confidence: 99%
“…These phenolic compounds also showed a protective effect against the activation of TLR-4 receptor cascade, TNF-alpha, and nitric oxide production. In addition, the extract limited the proinflammatory response and low-grade oxidative stress induced by LPS [58].…”
Section: Anti-inflammatory Activitymentioning
confidence: 99%